Prescribing target running intensities for high-school athletes: Can forward and backward running performance be autoregulated? - Uthoff, A.; Oliver, J.; Cronin, J.; Winwood, P.; Harrison, C. (Sports, 2018)
Target running intensities are prescribed to enhance sprint-running performance and progress injured athletes back into competition, yet is unknown whether running speed can be achieved using autoregulation. This study investigated the consistency of running intensities in adolescent athletes using autoregulation to self-select velocity. Thirty-four boys performed 20 m forward running (FR) and backward running (BR) trials at slow, moderate and fast intensities (40-55%, 60-75% and +90% maximum effort, respectively) on three occasions. Absolute and relative consistency was assessed using the coefficient of variation (CV) and intraclass correlation coefficients (ICC). Systematic changes in 10 and 20 m performance were identified between trials 1-2 for moderate and fast BR (p = 0.01) and during moderate BR over 20 m across trials 2-3 (p = 0.05). However, comparisons between trials 2-3 resulted in low typical percentage error (CV = 4.3%) and very good to excellent relative consistency (ICC = 0.87) for all running speeds and directions. Despite FR being significantly (p = 0.01) faster than BR at slow (26%), moderate (28%) and fast intensities (26%), consistency was similar in both running directions and strongest at the fastest speeds. Following appropriate familiarization, youth athletes may use autoregulation to self-select prescribed FR and BR target running intensities